2009
DOI: 10.1007/s10103-009-0670-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy on the fracture healing process

Abstract: Low-level laser therapy (LLLT) is a biophysical form of intervention in the fracture-repair process, which, through several mechanisms, accelerates the healing of fractures and enhances callus formation. The effect of laser on fracture healing is controversial. Some authors affirm that LLLT can accelerate bone formation by increasing osteoblastic activity. The objective of our study was to evaluate the effect of laser therapy on fracture healing. Thirty rabbits were subjected to tibial bone open osteotomies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 25 publications
4
53
0
12
Order By: Relevance
“…Despite the fact that lasers have demonstrated efficiency on osseous tissue healing [4,[10][11][12][13][14], in implantology, factors like high initial stability, implant geometry, and good bone quality, are more relevant for the quality of the implantbone interface than any additional therapeutic effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that lasers have demonstrated efficiency on osseous tissue healing [4,[10][11][12][13][14], in implantology, factors like high initial stability, implant geometry, and good bone quality, are more relevant for the quality of the implantbone interface than any additional therapeutic effort.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, authors proposed variations of the technique for bringing the implant into function and reduce the osseointegration time, by altering the texture of the titanium implant surface [1][2][3]. The use of low-level lasers has been suggested as another way of accelerating and improving the bone tissue healing process [4]. Laser light irradiation has been applied in the medical field and has biostimulatory effects on wound healing, collagen synthesis, and fibroblast proliferation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered a noninvasive, safe technique to stimulate osteogenesis [23,24]. Several previous studies have shown that LLLT could increase both osteoblast and osteoclast activities, together with stimulating the formation of callus and new bone matrix [25][26][27][28]. Of note, LLLT alone as a treatment modality in surgical defects enhanced faster and a greater area of bone formation compared to the PRF treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…The objective of our study was to evaluate the effect of laser therapy on fracture healing. [2] Low-level laser therapy is a clinically well established tool for enhancement of wound healing. In vitro studies have also shown that low level laser therapy has a biostimulatory effect on cells of different origin [3] Bone healing differs from that of soft tissues because of its morphology and composition.…”
Section: Introductionmentioning
confidence: 99%
“…Their characteristics include the absence of thermal and deleterious effects to the human body, promoting bio-stimulation of cells and thereby improving regenerative capacity. [1][2][3][4][5] This paper reports recent follow up for tibia bone fracture case with delayed fracture healing, reporting the observations on the effect of LLLT on bone fracture healing.…”
Section: Introductionmentioning
confidence: 99%